Safety confirmation of induced pluripotent stem cell-derived cardiomyocyte patch transplantation for ischemic cardiomyopathy: first three case reports - Kawamura, Takuji; Ito, Yoshito; Ito, Emiko; Takeda, Maki; Mikami, Tsubasa; Taguchi, Takura; Mochizuki-Oda, Noriko; Sasai, Masao; Shimamoto, Tomomi; Nitta, Yukako; Yoshioka, Daisuke; Kawamura, Masashi; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction With the expected increase in patients with heart failure and ischemic 15 cardiomyopathy, the development of myocardial regenerative medicine using cell transplantation as a novel treatment method is progressing. This first-in-human clinical trial aimed to confirm the safety of cardiomyocyte patch transplantation derived from allogeneic induced pluripotent stem (iPS) cells based on the results of several preclinical studies. Study design The inclusion criteria were left ventricular ejection fraction of 35% or less; heart failure symptoms of New York Heart Association class III or higher despite existing therapies such as revascularization; and a 1-year observation period that included a 3-month immunosuppressive drug administration period after transplantation of iPS cell-derived cardiomyocyte patches to evaluate adverse events, cardiac function, myocardial blood flow, heart failure symptoms, and immune response. Results In the first three cases of this trial, no transplanted cell-related adverse events were observed during the 1-year observation period, and improvement in heart failure symptoms was observed. In addition, improvements in left ventricular contractility and myocardial blood flow were observed in two of the three patients. Regarding immune response, an increase in transplant cell-specific antibody titer was observed in all three patients after immunosuppressive drug administration. In one patient with poor improvement in cardiac function and myocardial blood flow, an increase in antibody titer against HLA-DQ was observed even before cell transplantation. Conclusions Our case findings demonstrate that the transplantation of iPS cell-derived cardiomyocyte patches for ischemic cardiomyopathy can be safely performed; however, further investigation of the therapeutic effect and its relationship with an immune response is needed by accumulating the number of patients through continued clinical trials.